The drugs don't sell: DIY heart health and the over-the-counter statin experience. (April 2015) - Will, Catherine M.; Weiner, Kate
Abstract: This paper draws on a study of over-the-counter statins to provide a critical account of the figure of the 'pharmaceutical consumer' as a key actor in the pharmaceuticalisation literature. A low dose statin, promising to reduce cardiovascular risk, was reclassified to allow sale in pharmacies in the UK in 2004. We analysed professional and policy debates about the new product, promotional and sales information, and interviews with consumers and potential consumers conducted between 2008 and 2011, to consider the different consumer identities invoked by these diverse actors. While policymakers constructed an image of 'the citizen-consumer' who would take responsibility for heart health through exercising the choice to purchase a drug that was effectively rationed on the NHS and medical professionals raised concerns about 'a flawed consumer' who was likely to misuse the product, both these groups assumed that there would be a market for the drug. By contrast, those who bought the product or potentially fell within its target market might appear as 'health consumers', seeking out and paying for different food and lifestyle products and services, including those targeting high cholesterol. However, they were reluctant 'pharmaceutical consumers' who either preferred to take medication on the advice of a doctor, or sought to minimize medicine use. In comparison to previous studies, our analysis builds understanding of individual consumers in a market, rather than collective action for access to drugs (or, less commonly, compensation for adverse effects). Where some theories of pharmaceuticalisation have presented consumers as creating pressure for expanding markets, our data suggests that sociologists should be cautious about assuming there will be demand for new pharmaceutical products, especially those aimed at prevention or asymptomatic conditions, even in burgeoning health markets. Highlights: Policy makers, professionals and the manufacturer anticipated a willing market for over the counter statins. This looked like a case of pharmaceuticalisation, increasing indications for and availability of a preventive drug. However consumer demand was limited and people preferred to access non-pharmaceutical markets for heart health. As individuals, consumers continued to look to doctors for cholesterol testing and management.